New replacement name for Tricella Catalano & Dietrich, 2017 (Hemiptera: Cicadellidae: Typhlocybinae) - Catalano, María Inés; Dietrich, Christopher H. (Zootaxa, 2017)
We recently established the leafhopper genus Tricella with the type species Tricella antonellae from Ecuador (Catalano & Dietrich 2017). Unfortunately, Tricella n.gen is junior homonym of Tricella Daniels, 1975 (Diptera). Therefore, we propose a new replacement name Carpaneura nom. nov. for Tricella Catalano & Dietrich, 2017 as required by Article 60 of the International Code of Zoological Nomenclature. The genus is named in honor of the first author’s husband, Pablo Carpane. The name combines his family name with the suffix of the type genus of the tribe and is treated as a feminine noun. Replacement of the junior homonym also requires the following new combination for the originally designated type species: Carpaneura antonellae (Catalano & Dietrich), comb. nov.